(untitled) (INNOVATIVE ECONOMY, 2026)
Bryk M.M. FEATURES OF MANAGEMENT ACCOUNTING ORGANIZATION AT AGRICULTURAL ENTERPRISES AND CHALLENGES IN ITS IMPLEMENTATION Purpose. The aim of the article is an analysis of the main challenges in implementing and operating management accounting at enterprises in the agricultural sector, as well as identifying areas for improving its organization under current economic conditions. Methodology of research. The methodological basis of the study consists of general scientific and specialized methods for analysing economic processes. The monographic method was used in reviewing scientific works by domestic and foreign scholars on the theoretical foundations of management accounting. The analytical method was applied to study the current state of management accounting organization in agricultural enterprises and to identify factors hindering its implementation. The comparative method was used to contrast traditional and functional approaches to management organization, as well as various approaches to cost classification. The abstract and logical method was applied to generalize the research results, formulate conclusions, and develop proposals for improving the management accounting system. The systematic approach allowed for a comprehensive assessment of the interrelationship between accounting and analytical support and the management process of agricultural enterprises. The informational basis of the study consisted of legislative and regulatory acts of Ukraine, scientific works by domestic and foreign scholars, as well as practical materials on the activities of agricultural enterprises. Findings. This article examines the current state of management accounting in agricultural enterprises and identifies the main factors hindering its implementation. These include the inadequacy of regulatory and methodological support, insufficient professional training of specialists, a traditional approach to management, and limited use of modern methods of cost accounting and analysis. The article substantiates the need to improve the management accounting system by introducing a functional approach to management, developing internal reporting, modernizing the Chart of Accounts, and applying modern cost calculation methods. It is established that an effective management accounting system will contribute to improving information support, optimizing costs, and enhancing the efficiency of agricultural enterprise management. Originality. Approaches to organizing management accounting in agricultural enterprises have been improved by substantiating the need to establish a separate class of accounts for management accounting purposes, refining the cost classification system, and implementing a functional approach to enterprise management. Theoretical provisions regarding the role of management accounting as an integrated accounting and analytical system focused on providing information support for strategic and operational management have been further developed. Practical value. The practical significance of the obtained results lies in identifying areas for improving the management accounting system in agricultural enterprises. Implementing the proposed approaches will help improve the quality of accounting and analytical support for management, enhance cost control, increase the efficiency of resource utilization, and ensure more informed management decision-making in an unstable economic environment. Key words: management accounting, agricultural enterprises, cost accounting, management decisions, internal reporting, cost calculation, information support, financial stability, functional management, agricultural sector.